Calcium Signalling and Disease Molecular pathology of calcium - Carafoli, Ernesto; Brini, Marisa; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2007)
This topic is a new entry in the area of cellular calcium signaling: yet, it now spans the entire area, with discoveries that cover both genetic and acquired pathologies, even offering glimpses in the direction of therapy. Cellular calcium homeostasis, and thus calcium signalling, is mainly regulated by membrane intrinsic proteins and calcium sensor proteins. Both classes may be involved in pathological processes that affect both human and animals, ranging from common and important diseases (e.g. migraine, diabetes, epilepsia, manic depression, infertility, various types of cancer, Alzheimer’s disease, muscular dystrophy) to rare genetic conditions (e.g., a number of genetic heart conditions, autoimmune retinopathies, night blindness, hereditary amyloid polyneuropathy, malignant hyperthermia, cerebellar ataxia, atherothrombotic disease). Clearly, the topic has now become not only very large, but also very stimulating. Its extensive critical coverage is likely to eventually stimulate fruitful interdisciplinary discussions.
Annexinopathies -- Calpains and Human Disease -- Gelsolin and Diseases -- Guanylate Cyclase-Activating Proteins and Retina Disease -- Pathologies Involving the S100 Proteins and Rage -- The Calcium-Sensing Receptor: Physiology, Pathophysiology and Car-Based Therapeutics -- Physiological Roles Of The Ca2+/Cam-Dependent Protein kinase Cascade In Health and Disease -- Calcium Channelopathies: Voltage-Gated Calcium Channels -- Trp Channels In Disease -- Diseases associated with altered ryanodine receptor activity -- Inositol 1,4,5-tripshosphate receptor, calcium signalling and huntington’s disease -- Serca pumps and human diseases -- The plasma membrane calcium ATPase and disease -- Diseases involving the Golgi calcium pump -- Calcium signalling and cancer cell growth -- Calcium Misregulation and the Pathogenesis of Muscular Dystrophy -- Calcium and Cell Death -- Calcium and Cell Death: The Mitochondrial Connection -- Role of Calcium in the Pathogenesis of Alzheimer’s Disease and Transgenic Models -- Calcium and Cardiomyopathies -- Calcium Signalling and Calcium Transport in Bone Disease.
Keywords: Human genetics; Molecular biology; Biochemistry; Neurobiology; Human Genetics; Molecular Medicine; Biochemistry, general; Neurobiology